Handwashing Practices among Secondary Level Students: A Case from Community Schools in Bardiya District - Sharma, Mohan Kumar; Pant, Indira; Khanal, Shanti Prasad; Aryal, Bhagwan (Education and Development, 2024)
Handwashing practices with soap and water protects from many infectious diseases. The objective of this study has to assess handwashing practices among secondary level students from four community schools in Bardiya district. This study applied a quantitative, cross-sectional research design. A total of 384 students from grade IX to grade XII of Badiya district took part in the study. The data were collected using a structured questionnaire survey tool and were descriptively analyzed. More than half (50.52%) of the students were not able to follow the handwashing procedure correctly, though they articulated the appropriate conditions for handwashing. Of them, before eating and after using the toilet were most popular with a weightage of 73.7% and 70.3%, respectively. Following this, most of the participants (66.7%) indicated that the appropriate handwashing times were after touching garbage of animals and after coughing and sneezing (51%). A high majority (80.2%) revealed after using toilet as the normal handwashing time, whereas for 77.9%, it was after having food. A majority (73.2%) of them responded water and soap as commonly used handwashing materials. Concerning the handwashing practices, half (50.8%) of the students reported that they always washed their hands before food. A majority (56.8%) of the reported that they always washed their hands after using toilet. It was also found that the students had poor handwashing practices before having food and after using toilet. Thus, handwashing classes are strongly felt needed for the students of the surveyed school.